FACTORS ASSOCIATED WITH SILENT ISCHEMIA IN TYPE 2 DIABETIC PATIENTS - A, Vashisth; S, Sharma; R N, Patel; P K, GUPTA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The present study was conducted to study the role of treadmill testing (TMT) in identifying silent ischemia in diabetic patients and to assess factors associated with silent ischemia in them. Methods: The study was a hospital-based cross-sectional study where 60 patients with type 2 diabetes between the age 40 and 60 years without an established clinical diagnosis of coronary artery disease attending medical OPD were included in the study. The TMT was done using a computerized CTMT machine with built-in protocols. Continuous electrocardiogram (ECG) recordings were taken. Results: The prevalence of silent myocardial ischemia in type 2 asymptomatic diabetes mellitus in this study was found to be 28.3%. Smoking, higher age, alcohol intake, and duration of DM were found to be significantly associated with silent myocardial ischemia. Conclusion: Thus, we conclude that the prevalence of silent myocardial ischemia is more common in diabetics. Early screening of asymptomatic patients with type 2 diabetes mellitus with the help of TMT for evidence of silent myocardial ischemia may prevent catastrophic cardiac events.